Thermoset composites containing crosslinked imide extended compounds.

JP2025504846APending Publication Date: 2025-02-19ROGERS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024543002
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-19
Filing Date
2023-01-10
Publication Date
2025-02-19

Smart Images

  • Figure 2025504846000001_ABST
    Figure 2025504846000001_ABST
Patent Text Reader

Abstract

In one embodiment, the thermosetting composition includes an imide-extended compound and a reactive monomer that is free radical crosslinkable with the reactive end groups of the imide-extended compound to produce a crosslinked network. A thermosetting composite can be derived from the thermosetting composition, and a multilayer article can include the thermosetting composite in the form of a layer. The article can be an antenna, a bond ply, a dielectric film of a stack / rewiring layer of a semiconductor substrate, a circuit board, a resin-coated copper foil (RCC), or a flexible core.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 63 / 300,676, filed January 19, 2022, which is incorporated by reference in its entirety. [Background technology]

[0002] High performance materials can benefit from having low loss, low lamination temperature, and good flow, among other desirable properties. For example, desirable attributes for a circuit bond ply or thin film deposit are to have a low thickness with acceptable handling properties, be tack-free, have no to low odor, have a sufficient shelf life at room temperature, have a reduced lamination temperature, be compatible with conventional circuit production processes including semi-additive processes, have satisfactory resin packing and flow using sufficient lamination pressures and temperature ramp rates, have a low z-axis coefficient of thermal expansion, and / or have good peel strength to copper. Such materials are difficult to develop because changing the composition to improve one property often results in the detriment of another property.

[0003] In view of the above, there remains a need for improved high performance dielectric composite materials with a tunable range of properties. In particular, there is a need for materials that have an improved combination of properties including high peel strength to metal foils and low dissipative losses, among other desirable electrical, thermal, and physical properties. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] "Split Post Dielectric Resonator (SPDR) Technique for Precise Measurements of Laminar Dielectric Specimens" (IEEE Xplore Conference Paper, February 2000) Summary of the Invention [Problem to be solved by the invention]

[0005] SUMMARY OF THE DISCLOSURE Disclosed herein are thermoset composite materials, methods of making, and articles derived therefrom. [Means for solving the problem]

[0006] In one embodiment, the thermosetting composition has the following structure:

[0007] [ka]

[0008] wherein R and Q are each independently a divalent substituted or unsubstituted aliphatic, alkenyl, aromatic, heteroaromatic, or divalent siloxane group, and each R2 independently includes a reactive alkenyl end group. and an imide-extended compound of a reactive end group of the imide extended compound and a reactive monomer that is free radical crosslinkable to produce a crosslinked network; Includes.

[0009] These and other attributes are exemplified by the following figures, detailed description, and claims.

[0010] The figures are illustrative of examples and are not intended to limit devices manufactured in accordance with the present disclosure to the materials, conditions, or process parameters referred to herein. [Brief description of the drawings]

[0011] [Figure 1] 1 is a photographic image of the imide-extended composite material of Example 1 lying flat on a table. [Diagram 2] 1 is a photographic image of the PPO composite of Example 2 being bent. [Diagram 3] 1 is a photographic image of three glass substrates of Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Composites derived from thermosetting compositions containing imide extended compounds and reactive monomers have been developed that can exhibit a good balance of properties and can be adapted for use in a variety of applications including prepregs, resin coated conductive (RCC) layers, circuit boards, bond plies, coating films, deposition materials, deposition films, or flexible cores.

[0013] The imide extended compound has the formula (1) or the formula (2):

[0014] [ka]

[0015] wherein each R is independently a divalent substituted or unsubstituted aliphatic, alkenyl, aromatic, or heteroaromatic group, or a divalent siloxane group; each Q is independently a divalent or tetravalent substituted or unsubstituted aliphatic, alkenyl, aromatic, or heteroaromatic group, or a divalent siloxane group; and each R2 independently includes a reactive alkenyl end group. The compound may include a compound having at least one of the following structures:

[0016] R may be linear, branched, or cyclic. R may be a hydrocarbon group. R may contain 1 to 100 carbon atoms, or 10 to 90 carbon atoms, or 20 to 40 carbon atoms. R may be, for example, a branched alkylene group or a branched aliphatic group having 20 to 40 carbon atoms. R may be, for example, a C1~50 , or C 30~40 R may be a substituted or unsubstituted C 1~50 , or C 30~40 It may be a dihydric alkane, optionally containing one or more cyclic alkane moieties, and optionally containing 0 to 3 unsaturations. When R contains a branched alkylene group or a branched aliphatic group, the flexibility of the composite material may be improved.

[0017] Q may be a hydrocarbon group having 1 to 100 carbon atoms, 2 to 50 carbon atoms, or 4 to 10 carbon atoms. Q may be, for example, a substituted or unsubstituted siloxane group derived from dimethylsiloxane, methylphenylsiloxane, or diphenylsiloxane. Q may be, for example, an acyl group, an alkyl group, an alkenyl group, an alkoxy group, an alkynyl group, an amido group, an amino group, an aryl group, an aryloxy group, a carbamate group, a carboxyl group, a cyano group, a cycloalkyl group, a haloalkyl group, a halogen atom, a heterocyclic group, a heteroaryl group, a hydroxyl group, a mercapto group, a nitro group, a nitroso group, -C(O)H, -NR x C(O)-N(R x )2, -OC(O)-N(R x )2, an oxyacyl group, or a sulfonamide group, where R x can be a hydrogen atom or an alkyl group. Q can be a substituted or unsubstituted tetravalent organic group having 1 to 100 carbon atoms, or 2 to 50 carbon atoms, or 4 to 10 carbon atoms.

[0018] Q can be, for example, a tetravalent aryl group resulting in a repeating group having the formula Q1. Q1 can result in composite materials with increased mechanical strength compared to non-aromatic groups. Q1 can be derived from pyromellitic anhydride. Q can be, for example, a tetravalent aryloxy group resulting in a repeating group having the formula Q2. Q2 can be derived from 4,4'-oxydiphthalic anhydride.

[0019] [ka]

[0020] R2 can be a maleimide group, a citraconimide group, a styryl group, a vinylbenzyl group, a vinyl group, an allyl group, an alkynyl group, a propargyl ether group, a cyano group, a vinyl ether group, a vinyl ester group, an acrylate group, a methacrylate group, an oxazoline group, a benzoxazine group, or a methylnorbornene group.

[0021] The imide extended compound can include a bismaleimide compound of formula (3).

[0022] [ka]

[0023] The imide extended compound can include a bisstyryl compound of formula (4).

[0024] [ka]

[0025] The imide extended compound can include a bisvinylbenzyl compound of formula (5).

[0026] [ka]

[0027] The imide extended compound can include a bisvinyl compound of formula (6).

[0028] [ka]

[0029] The imide extended compound can include a bis-allyl compound of formula (7).

[0030] [ka]

[0031] The imide extended compound can include a compound having the formula (8).

[0032] [ka]

[0033] The imide extended compound can have a degree of polymerization (eg, n as exemplified in Formula 8) of 1-100, or 2-10.

[0034] The thermosetting composition can include from 10 to 90 volume percent (vol %), or from 25 to 75 vol %, or from 30 to 50 vol % of the imide extended compound, based on the total volume of the composition.

[0035] The thermosetting composition includes a reactive monomer that is free radical crosslinkable with the reactive end groups of the imide extended compound to produce a crosslinked network. The reactive monomer can include triallyl (iso)cyanurate. The triallyl (iso)cyanurate includes at least one of triallyl isocyanurate and triallyl cyanurate, which are exemplified in formula (A) and formula (B), respectively.

[0036] [ka]

[0037] The composition may comprise from 1 to 40 vol%, or from 10 to 35 vol%, or from 20 to 30 vol% of the reactive monomer, based on the total volume of the composition.

[0038] Other copolymerizable monomers include, but are not limited to, vinyl aromatic monomers, such as substituted and unsubstituted monovinyl aromatic monomers, such as styrene, 3-methylstyrene, 3,5-diethylstyrene, 4-n-propylstyrene, alpha-methylstyrene, alpha-methylvinyltoluene, parahydroxystyrene, 4-acetoxystyrene, paramethoxystyrene, alpha-chlorostyrene, alpha-bromostyrene, dichlorostyrene, dibromostyrene, tetra-chlorostyrene, and the like, as well as substituted and unsubstituted divinylaromatic monomers, such as divinylbenzene, divinyltoluene, and the like. Combinations comprising at least one of the foregoing copolymerizable monomers may also be used.

[0039] Still other optional crosslinkers are trimethylolpropane trimethacrylate (TMP TMA), pentaerythritol tetraacrylate (PETA) or isocyanuric acid tris(2-acryloyloxyethyl)ester (THEIC triacrylate), diallyl phthalic acid, and other multifunctional (meth)acrylate monomers (e.g., SARTOMER resins available from Sartomer Corporation, Exton, PA, USA), as well as combinations comprising at least one of the foregoing, all of which are commercially available.

[0040] The thermosetting composition may include a free radical initiator, which may thermally decompose to form free radicals, which then initiate polymerization of ethylenically unsaturated double bonds within the composition. These initiators generally provide weak bonds, e.g., bonds with small dissociation energy. The free radical initiator may include at least one of a peroxide initiator, an azo initiator, a carbon-carbon initiator, a persulfate initiator, a hydrazine initiator, a hydrazide initiator, a benzophenone initiator, or a halogen initiator. The free radical initiator may include 2,3-dimethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, or poly(1,4-diisopropylbenzene). The initiator may include at least one of an organic peroxide, e.g., dicumyl peroxide, t-butyl perbenzoate, α,α'-di-(t-butylperoxy)diisopropylbenzene, or 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne. Initiators include, for example, α-hydroxyketones, phenylglyoxylic acid, benzil dimethyl-ketal, α-aminoketones, monoacylphosphines (MAPO), bisacylphosphines (BAPO), diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO), phosphine oxides, or metallocenes, and may be photosensitive.

[0041] The free radical initiator can include at least one of methyl ethyl ketone peroxide, cyclohexanone peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,2-bis(t-butylperoxy)butane, t-butyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, or 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, octanoyl peroxide, isobutyryl peroxide, dibenzoyl peroxide, peroxydicarbonate, α,α'-azobis(isobutyronitrile), a redox initiator, or an acetyl azide.

[0042] The free radical initiator can be present in an amount of 0.1 to 5 weight percent (wt%), or 0.1 to 1.5 wt%, based on the total weight of the thermosetting composition. The free radical initiator can be present in an amount of 0 to 10 vol%, or 2 to 8 vol%, or 0.1 to 3 vol%, based on the total volume of the composition.

[0043] The thermosetting composition can include fused silica. All or a portion of the fused silica can be chemically coupled to the crosslinked network. For example, the fused silica can include a surface treatment to hydrophobize the fused silica. The surface treatment can be formed by grafting a silane onto the fused silica. The silane can include a reactive end group that can be chemically coupled to the crosslinked network.

[0044] The silane can include at least one of a phenylsilane or a fluorosilane. The phenylsilane can include at least one of p-chloromethylphenyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltrichlorosilane, phenyl-tris-(4-biphenylyl)silane, (phenoxy)triphenylsilane, or a functionalized phenylsilane. The functionalized phenylsilane can be represented by the formula R'SiZ 1 R 2 Z 2 where R' is an alkyl group having 1 to 3 carbon atoms, -SH, -CN, -N3, or hydrogen; Z 1 and Z 2 are each independently chlorine, fluorine, bromine, an alkoxy having six or fewer carbon atoms, NH, -NH2, or -NR2'; R 2 teeth,

[0045] [ka]

[0046] wherein each of the S-substituents, S1, S2, S3, S4 and S5, is independently hydrogen, alkyl having 1 to 4 carbon atoms, methoxy, ethoxy, or cyano, with the proviso that at least one of the S-substituents is other than hydrogen, and if a methyl or methoxy S-substituent is present, then (i) at least two S-substituents are other than hydrogen, (ii) two adjacent S-substituents together with the phenyl nucleus form a naphthalene or anthracene group, or (iii) three adjacent S-substituents together with the phenyl nucleus form a pyrene group, and X is -(CH2) n - group, where n is 0 to 20, or, if n is not 0, 10 to 16, in other words, X is an optional spacer group. The term "lower" with respect to a group or compound means 1 to 7 and / or 1 to 4 carbon atoms.

[0047] Fluorosilanes may be beneficial compared to other silanes because fluorine atoms have the lowest polarizability of all atoms, so fluorinated molecules exhibit very weak intermolecular dispersion forces. As a result, fluorinated molecules are significantly both hydrophobic and oleophobic at the same time. To fully utilize the hydrophobing ability of fluorinated compounds in composites, instead of in-situ silanizing fused silica in the composite, fused silica may be pretreated with fluorinated silanes prior to forming the composite. Pretreatment of fused silica may be preferential due to the oleophobicity (immiscibility) of fluorinated silanes in the composite. It should be noted that just as it may be beneficial to pretreat fused silica with fluorinated silanes prior to forming the composite, it may also be beneficial to pretreat fused silica with other hydrophobic silanes.

[0048] Fluorosilane coatings have the formula: CF3(CF2) nThe fluorosilanes may be formed from perfluorinated alkylsilanes having the formula -CH2CH2SiX, where X is a hydrolyzable functional group and n=0 or an entire integer. ... The fluorosilane may include at least one of perfluorooctyltriethoxysilane, (heptadecafluoro-1,1,2,2-tetrahydrododecyl)-1-methyldichlorosilane, (heptadecafluoro-1,1,2,2-tetrahydrododecyl)-1-trichlorosilane, (heptadecafluoro-1,1,2,2-tetrahydrododecyl)-1-dimethylchlorosilane, (heptafluoroisopropoxy)propylmethyldichlorosilane, 3-(heptafluoroisopropoxy)propyltrichlorosilane, 3-(heptafluoroisopropoxy)propyltriethoxysilane. The fluorosilane may include perfluorooctyltriethoxysilane.

[0049] The silane may include at least one of an aminosilane or a silane containing a polymerizable functional group such as an acrylic or methacrylic group. Examples of aminosilanes include N-methyl-γ-aminopropyltriethoxysilane, N-ethyl-γ-aminopropyltrimethoxysilane, N-methyl-β-aminoethyltrimethoxysilane, N-methyl-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldimethoxysilane, N-(β-N-methylaminoethyl)-γ-aminopropyltriethoxysilane, aminoethylaminopropyltrimethoxysilane, N-(γ-aminopropyl)-γ-aminopropylmethyldimethoxysilane, (2-ethylpiperidino)(5- At least one of N-(γ-aminopropyl)-N-methyl-γ-aminopropyl methyl dimethoxysilane and γ-aminopropyl ethyl diethoxysilane aminoethyl aminotrimethoxysilane, or n-methyl piperazinophenyl dichlorosilane may be mentioned.

[0050] The fused silica may be functionalized with a functional group comprising at least one of a (meth)acrylate group, a vinyl group, an allyl group, a propargyl group, a butenyl group, a styryl group, or a vinylbenzyl group, and preferably the functional group of the functionalized fused silica comprises a (meth)acrylate group. The silane comprising a polymerizable functional group is represented by the formula R a x SiR b (3-x) R, wherein each R a are the same or different (e.g., the same), halogen (e.g., Cl or Br), C 1~4 Alkoxy (e.g., methoxy or ethoxy), or C 2~6 and each R b is C 1~8 Alkyl or C 6~12 Aryl (e.g., R bcan be methyl, ethyl, propyl, butyl, or phenyl), x is 1, 2, or 3 (e.g., 2 or 3), and R is -(CH) n OC(=O)C(R c )=CH2, where R c is hydrogen or methyl, and n is an integer from 1 to 6, or from 2 to 4. The silane can include at least one of methacrylsilane (3-methacryloxypropyltrimethoxysilane) or trimethoxyphenylsilane.

[0051] The fused silica may have a spherical structural morphology with a median diameter of 1 to 50 micrometers, 1 to 10 micrometers, or less than 1 micrometer. The fused silica may have a D90 particle size of 1 to 20 micrometers, or 5 to 15 micrometers. As used herein, particle size may be determined using dynamic light scattering.

[0052] The composition can include 10-70 vol%, or 20-60 vol%, or 30-55 vol% of fused silica based on the total volume of the composition. The composition can include 10-70 vol%, or 20-60 vol%, or 30-55 vol% of functionalized fused silica based on the total volume of the composition.

[0053] The thermosetting composition may contain ceramic fillers other than or in addition to fused silica, such as fumed silica, silane-treated fumed silica, titanium dioxide, barium titanate, strontium titanate, corundum, wollastonite, Ba2Ti9O 20The ceramic filler may comprise at least one of the following: hollow ceramic spheres, boron nitride, aluminum nitride, silicon carbide, beryllia, alumina, alumina trihydrate, magnesia, mica, talc, nanoclay, or magnesium hydroxide. The surface of the ceramic filler may also be modified using physical vapor deposition (PVD) and / or chemical vapor deposition (CVD, such as, but not limited to, atomic layer deposition (ALD). The ceramic filler may be present in an amount of 10-70 vol%, or 20-60 vol%, or 30-55 vol% of the fused silica, based on the total volume of the composition. The composition may comprise 10-70 vol%, or 20-60 vol%, or 30-55 vol% of the functionalized fused silica, based on the total volume of the composition.

[0054] The thermosetting composition can include 10-90 vol% of the imide-extended bismaleimide of formula 8, 1-40 vol% of triallyl (iso)cyanurate, 0.1-10 vol% of a free radical initiator, and 10-70 vol% of a methacrylate-functionalized fused silica, the volumes of which are based on the total volume of the thermosetting composition. Similarly, the thermosetting composite can include 10-90 vol% of the imide-extended bismaleimide of formula 8, 1-40 vol% of triallyl (iso)cyanurate, 0.1-10 vol% of a free radical initiator, and 10-70 vol% of a methacrylate-functionalized fused silica, the volumes of which are based on the total volume of the composite.

[0055] The thermosetting composition can include a flame retardant. The flame retardant can include at least one of a metal hydrate, an organic flame retardant, an organometallic flame retardant, or a halogenated flame retardant.

[0056] The metal hydrate may include a hydrate of at least one of metals, for example, Mg, Ca, Al, Fe, Zn, Ba, Cu, or Ni. As the hydrate of Mg, Al, or Ca, for example, at least one of aluminum hydroxide, magnesium hydroxide, calcium hydroxide, iron hydroxide, zinc hydroxide, copper hydroxide, nickel hydroxide, or a hydrate of calcium aluminate, gypsum dihydrate, zinc borate, zinc stannate, or barium metaborate may be used. As a composite of these hydrates, for example, a hydrate containing Mg and at least one of Ca, Al, Fe, Zn, Ba, Cu, or Ni may be used. The composite metal hydrate may be represented by the formula MgM x (OH) y where M is Ca, Al, Fe, Zn, Ba, Cu, or Ni, x is 0.1 to 10, and y is 2 to 32. The metal hydrate may have a volume average particle size of 1 to 500 nanometers (nm), or 1 to 200 nm, or 5 to 200 nm, or 10 to 200 nm, or the volume average particle size may be 500 nm to 15 micrometers, for example, 1 to 5 micrometers.

[0057] The organic flame retardant may include at least one of melamine cyanurate, a phosphorus-containing compound (e.g., melamine polyphosphate, an aliphatic or aromatic phosphinic acid, a diphosphinic acid, a phosphonic acid, a phosphazene, a phosphorous acid, a phosphine, or a phosphate), a polysilsesquioxane, or a siloxane. Any of the organic or organometallic flame retardants may be halogen-free.

[0058] The halogenated flame retardant can include at least one of hexachloroendomethylenetetrahydrophthalic acid (HET acid), tetrabromophthalic acid, dibromoneopentyl glycol, bis-pentabromophenylethane (commercially available as SAYTEX 8010), ethylene bistetrabromophthalimide (commercially available as SAYTEX BT93W), tetradecabromodiphenoxybenzene (commercially available as SAYTEX 120), or decabromodiphenyl oxide (commercially available as SAYTEX 102).

[0059] Flame retardants may be used in combination with synergists, for example, halogenated flame retardants may be used in combination with a synergist such as antimony trioxide, and phosphorus-containing flame retardants may be used in combination with a nitrogen-containing compound such as melamine.

[0060] The flame retardant particles may be coated or otherwise treated to improve dispersion and other properties. The flame retardant may be present in an amount of 5 to 25 vol%, or 8 to 20 vol%, based on the total volume of the composition. The composition may be flame retardant-free, for example, containing 0 to 0.5 vol%, or 0 vol% flame retardant, based on the total volume of the composition.

[0061] The thermosetting composition may include a solvent. The solvent may be selected to dissolve the thermosetting components, disperse the particulate additives and any other optional additives that may be present, and have a favorable evaporation rate for forming, drying, and b-staging. The solvent may include at least one of xylene, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), hexane, higher liquid linear alkanes (e.g., heptane, octane, or nonane), cyclohexane, cyclohexanone, isophorone, glycol ether PM, glycol ether PM acetate, ethyl lactate, or a terpene-based solvent. The solvent may include at least one of xylene, toluene, methyl ethyl ketone, methyl isobutyl ketone, or hexane. The solvent may include at least one of xylene or toluene. The solvent may be present in an amount of 2 to 80 wt%, or 40 to 60 wt%, or 2 to 5 wt%, based on the total weight of the thermosetting composition including the solvent. The thermosetting composition may comprise 20-98 wt% solids (all components other than the solvent), or 40-60 wt%, or 95-98 wt% solids, based on the total weight of the thermosetting composition including the solvent. The resulting composite may be free of solvent, e.g., only the amount remaining after the curing step. The composite may comprise 0-0.5 wt%, or 0-0.05 wt%, or 0 wt% solvent, based on the total weight of the composite including the solvent.

[0062] Composite materials formed from thermosetting compositions can include a reinforcing fabric (also referred to as a fabric or reinforcing layer). The fabric can include a fibrous layer including a plurality of thermally stable fibers. The fabric can be a woven fabric or a nonwoven fabric such as a felt. The fabric can reduce in-plane shrinkage of the composite material during curing. In addition, the use of a fabric can help the composite material have relatively high dimensional stability and mechanical strength (modulus of elasticity). Such materials can be more easily processed by methods in commercial use, such as lamination, including roll-to-roll lamination.

[0063] The fabric may include thermally stable fibers. The thermally stable fibers may include glass fibers such as at least one of lower dielectric constant, lower dissipation loss fibers such as E-glass, S-glass, D-glass, or NE-glass, L-glass, or quartz fibers. For example, thermally stable fibers with lower dielectric constant, lower dissipation factor such as NITTOBO NE available from Nitto Boseki Co., Ltd., Tokyo, Japan, or L-glass available from AGY Corporation, Aiken, South Carolina, or Shin-Etsu SQX available from Shin-Etsu Chemical Co., Ltd., Tokyo, Japan. The thermally stable fibers may include polymeric fibers such as high temperature polymer fibers, pulp, or fibrillated pulp. The polymeric fibers may include liquid crystal polymers such as VECTRAN available from Kuraray America Inc., Fort Mill, SC. The polymeric fibers may include at least one of polyetherimide (PEI), polyetherketone (PEK), polyetheretherketone (PEEK), polysulfone (PSU), polyethersulfone (PES or PESU), polyphenylene sulfide (PPS), polycarbonate (PC), poly m-aramid (fiber or fibrid), poly p-aramid, polyvinylidene difluoride (PVDF), or polyester (such as PET). The polymeric fibers may include at least one of liquid crystal polymer (LCP) fibers, aramid fibers, cyclic olefin copolymer (COC) fibers, or ultra-high molecular weight polyethylene (UHMWPE) fibers.

[0064] Thermally stable fabrics containing glass fibers may be plain or open weave and can be balanced. Open weaves can reduce signal skew and crosstalk, enhance impedance control, resistance to conductive anodic filament (CAF) growth, dimensional stability, prepreg yield, and be more suitable for laser drilling during circuit production. Fabrics can include open weave fabrics with lower dielectric constants and lower dissipation factors.

[0065] The thermosetting composition can be coated on one or both sides of the fabric and / or can be impregnated into the reinforcing layer, thereby integrating into the composite layer formed upon curing. The fabric can have a thickness of 5 to 100 micrometers, or 10 to 60 micrometers. The fabric can be present in an amount of 5 to 40 wt%, or 15 to 25 wt%, based on the total weight of the composite.

[0066] The composite material may have a peel strength to copper of greater than or equal to 0.35 kilograms per centimeter as determined in accordance with "Peel Strength of Metal Clad Laminates" (IPC-TM-650 2.4.8).

[0067] The composite material may have an average coefficient of thermal expansion in the z-direction of 40 parts per million per degree Celsius (ppm / °C) or less, or 35 ppm / °C or less, or 25 to 90 ppm / °C, or 60 to 85 ppm / °C, from -50 to 150°C, as determined in accordance with "Glass Transition Temperature and Thermal Expansion of Materials Used in High Density Interconnects (HDI) and Microvias - TMA Method" (IPC-TM-650 2.4.24.5).

[0068] The composite material may have a dielectric constant of 2.5 to 3.5, measured according to "Split Post Dielectric Resonator (SPDR) Method for Precision Measurements of Layered Dielectric Specimens" (IEEE Xplore Conference Paper, February 2000), at a temperature of 23 to 25° C., a relative humidity of 50% and a frequency of 10 gigahertz (GHz).

[0069] The composite material may have a dielectric loss of 0.0025 or less, or 0.0020 or less, or between 0.001 and 0.0025, measured according to "Split Post Dielectric Resonator (SPDR) Method for Precision Measurements of Layered Dielectric Specimens" (IEEE Xplore Conference Paper, February 2000) at a temperature of 23-25° C., a relative humidity of 50% and a frequency of 10 gigahertz (GHz).

[0070] The composite material may have a UL 94 V0 rating at a thickness of 84 to 760 micrometers as determined in accordance with Underwriter's Laboratory UL 94 safety standard "Flammability Test for Plastic Materials Used in Equipment Components."

[0071] The composite material may have an elastic modulus of 4 gigapascals (GPa) or less, or 2 GPa or less, or between 0.4 and 1.5 GPa, as determined in accordance with "Glass Transition and Elastic Modulus of Materials Used in High Density Interconnects (HDI) and Microvias - DMA Method" (IPC-TM-650 2.4.24.4).

[0072] The composite material may have a minimum melt viscosity of 100 to 3,000 poise, or 1,000 to 3,000 poise, or 2,000 to 2,900, or 150 to 300 poise, determined using parallel plate oscillatory rheology at a temperature ramp rate of 10° C. per minute.

[0073] The method of making a composite material can include curing a layer formed from a thermosetting composition. The curing can include at least one of increasing the temperature of the layer, exposing the layer to electron beam radiation, or exposing the layer to ultraviolet (UV) radiation. The method can further include at least one of forming the layer by casting the composition onto a release liner, casting the composition onto a metal foil such as copper or aluminum, or impregnating a reinforcing layer with the composition prior to the curing step.

[0074] Prepregs can be formed by treating a fabric with a thermosetting composition and partially curing (b-staging) the thermosetting composition. As used herein, the term b-staging can refer to (1) a thermosetting composition, optionally in a solvent carrier, being applied to (2) a surface, such as woven fiberglass, followed by (3) evaporation of any solvent carrier below the initiation temperature of polymerization, followed by (4) application of additional heat to (5) partially polymerize (or partially cure) the thermosetting composition, followed by (6) cooling to prevent the thermosetting composition from fully polymerizing. The step of partially curing the thermosetting composition can be particularly useful in applications where it is important to control the amount of resin flow that occurs when heat and pressure are applied to the b-stage system. After the b-stage system is formed, the b-stage system can be exposed to additional heat to fully cure the partially cured thermosetting composition. This final polymerization is often referred to as c-staging. An example of forming a composite through a partially cured composite is to first make a b-stage thermoset composition (otherwise known as a prepreg) and then either laminate the prepreg in the same facility to form a c-stage laminate or laminate the prepreg in a different facility. Lamination typically involves the application of both heat and pressure, often resulting in the formation of a multi-layer structure.

[0075] The thermosetting composition may be formed by mixing the various components in any order, optionally in the melt or in an inert solvent. Mixing may be by any suitable method, such as blending, mixing, or stirring. The components used to form the thermosetting composition may be mixed by dissolving or suspending the components in a solvent to provide a coating mixture or solution. Forming the prepreg may include holding the treated fabric at an elevated temperature for a time sufficient to evaporate the formulation solvent and at least partially cure (b-stage) the thermosetting composition. After forming the prepreg, the prepreg may be stored for a period of time before the material is fully cured, for example, during the fabrication of a circuit laminate or other circuit subassembly. In one type of construction, a multi-layer laminate may include two or more plies of prepreg between conductive layers.

[0076] Methods for treating the fabric with the thermosetting composition include, but are not limited to, for example, by dip coating or roll coating, optionally at elevated temperatures. Single ply prepregs can have thicknesses of 10 to 200 micrometers, or 30 to 150 micrometers. Note that if a single ply unclad material is desired, then the thermosetting composition can be fully cured to form a composite material.

[0077] The method for casting the unreinforced film layer without reinforcing fabric, such as a stacked film or bond ply containing the thermosetting composition, can be performed by, for example, slot die or knife over roll application techniques, without limitation. The thermosetting composition can be cast horizontally onto a carrier film that is thermally robust and of suitable tensile strength. For example, in a roll-to-roll conveyorized process, the carrier film carries the unreinforced film layer through an oven and acts as an interleaf for the unreinforced film layer when wound up. The carrier film can also support the unreinforced film layer through subsequent sheeting, paneling, and final use handling. The carrier film, sometimes referred to as a release liner, can exhibit a special surface energy range that ensures defect-free liquid film coating of the thermosetting composition, fixation (adhesion) of the resulting unreinforced film layer to the carrier film through an oven (because the unreinforced film layer is dried and / or potentially b-staged), and easy peeling of the unreinforced film layer from the carrier film just prior to final use.

[0078] Two or more prepregs and / or two or more unreinforced film layers can be laminated together to form a composite material. Circuit materials including composite materials can similarly be formed by laminating at least one ply of prepreg and / or one ply of unreinforced film layer and at least one conductive layer.

[0079] Laminating can involve laminating a layer structure including a dielectric stack of one or more prepregs and / or a layer structure including a dielectric stack of one or more non-reinforced film layers, a conductive layer, and any intermediate layers between the dielectric stack and the conductive layer to form a laminate. Similarly, if desired, the layer structure can include a dielectric stack without a conductive layer. The conductive layer may be in direct contact with the dielectric stack without an intermediate layer. The dielectric stack can include 1 to 200 plies, or 2 to 50, or 5 to 100 plies, and at least one conductive layer can be disposed on the outermost side of the dielectric stack. The layer structure can then be placed in a press, e.g., a vacuum press, under pressure and temperature suitable for adhering the layers for a suitable time to form a laminate. Optionally, the layer structure can be roll-to-roll laminated or autoclaved.

[0080] The lamination and optional curing steps can be by a one-step process, for example using a vacuum press, or can be by a multi-step process. In a one-step process, the layer structure can be placed in a press, subjected to lamination pressure, and heated to a lamination temperature. The lamination temperature can be 100-390°C, or 100-250°C, or 100-240°C, or 100-175°C, or 150-170°C. The lamination pressure can be 1-3 megapascals (MPa), or 1-2 MPa, or 1-1.5 MPa. The lamination temperature and pressure can be maintained for a desired dwell (soak) time, for example, 5-150 minutes, or 5-100 minutes, 10-50 minutes, and then optionally cooled at a controlled cooling rate (with or without applied pressure), for example, to 150°C or less.

[0081] The conductive layer may be applied by laser direct structuring, where the composite material may include a laser direct structuring additive, and the laser direct structuring may include irradiating a surface of the substrate using a laser, forming passages of the laser direct structuring additive, and applying a conductive metal to the passages. The laser direct structuring additive may include metal oxide particles (such as titanium oxide and copper chromium oxide). The laser direct structuring additive may include spinel-based inorganic metal oxide particles, such as copper spinel. The metal oxide particles may be coated with a composition including, for example, tin and antimony (e.g., 50-99 wt% tin and 1-50 wt% antimony, based on the total weight of the coating). The laser direct structuring additive may include 2-20 parts of additive per 100 parts of composition. The irradiation may be performed with a YAG laser having a wavelength of 1,064 nanometers under an output power of 10 watts, a frequency of 80 kilohertz, and a speed of 3 meters per second. The conductive metal may be applied using a semi-additive plating process, for example in an electroless and / or electrolytic plating bath containing copper.

[0082] The conductive layer may comprise at least one of stainless steel, copper, gold, silver, aluminum, zinc, tin, lead, nickel, or transition metals such as palladium. There is no particular limitation on the thickness of the conductive layer, nor any limitation on the shape, dimensions, or surface texture of the conductive layer. The conductive layer may have a thickness of 3 to 200 micrometers, or 9 to 180 micrometers. When two or more conductive layers are present, the thickness of the two layers may be the same or different. The conductive layer may comprise a copper layer. Suitable conductive layers include, but are not limited to, thin layers of conductive metals such as copper foils currently used in forming circuits, for example, electro-deposited or annealed copper foils such as highly oriented grain structure annealed copper foils exhibiting flexural flexibility (high flexural fatigue resistance), such as HA, HA-V2, and HG, commercially available from JX Metals Corporation, Tokyo, Japan.

[0083] The copper foil may have a root mean square (RMS) roughness of 5 micrometers or less, or 0.1 to 3 micrometers, or 0.05 to 0.7 micrometers. As used herein, the roughness of the conductive layer may be determined by atomic force microscopy in contact mode, reported in micrometers as Rz calculated by subtracting the sum of the five lowest valley values ​​from the sum of the five highest peak values ​​measured, then dividing by five (JIS (Japanese Industrial Standards)-B-0601), or the roughness may be determined using white light scanning interferometry in non-contact mode, reported in micrometers as height parameters Sa, Sq, Sz using a stitching technique (ISO 25178) to characterize the surface topography and texture of the treated side. The copper foil can be a zinc-free battery foil layer having a low profile treated side roughness, for example, having at least one of Sa of 0.05-0.4, Sq of 0.01-1, Sz of 0.5-10, or Sdr of 0.5-30%.

[0084] The article may include a composite material. The article may include a multi-layer article that may include a composite layer and at least one additional layer. The composite layer may have a thickness of 5 to 200 micrometers, or 5 to 75 micrometers. The multi-layer article may further include at least one of a copper layer, a glass layer, a liquid crystal polymer (LCP) layer, an ultra-low CTE polyimide film layer, a fluoropolymer layer, a ceramic layer, a polyaramid layer, an epoxy layer, or a polyether layer.

[0085] The article may be a prepreg, a resin coated conductive (RCC) layer, a circuit board, a bond ply, a coating film, a stacked material, a stacked film, or a flexible core. The composite material may be an unclad or declad dielectric layer, a single clad dielectric layer, or a dual clad dielectric layer. The article may be a dielectric film of a stack / redistribution layer of a semiconductor substrate.

[0086] A dual clad laminate has two conductive layers, one on each side of the composite material. The circuit material can include a composite material. The circuit material is a type of circuit subassembly with a conductive layer, e.g., copper, fixedly attached to the composite material. The circuit can be provided by patterning the conductive layer, e.g., by printing and etching. A multi-layer circuit can include multiple conductive layers, at least one of which contains a conductive wiring pattern. Typically, a multi-layer circuit is formed by laminating two or more materials together in proper alignment using bond plies with the application of heat or pressure, at least one of which contains a circuit layer. The circuit material can itself function as an antenna.

[0087] The bond ply may be unreinforced and thus does not include a reinforcing fabric. The bond ply may be, for example, an adhesive used in printed circuit materials. The bond ply may be used to bond two adjacent layers. The bond ply may have good flow properties so that a layer having a thickness of less than 15 micrometers may be formed. The bond ply may be flexible and may be used in flex or rigid-flex applications.

[0088] The deposited materials may be used in semiconductor applications such as, but not limited to, forming one or more redistribution layers (RDLs). For example, the composite materials are particularly suitable for advanced packaging substrates including glass cores such as antenna-in-package (AiP), system-in-package (SiP) and / or system on an integrated chip (SoIC). Multiple integrated chips may be encapsulated in one or more chip carrier packages as part of a package-on-package (PoP). Such packages may integrate radio frequency (RF), analog, or digital functions and include active and passive components in a single module. Applications for such devices include eMBB, URLLC, massively multi-channel communications (mMTC) and high frequency, high speed machine-to-cloud communications. Substrates for such devices typically include low temperature co-fired ceramics (LTCC), multi-layered organics including prepregs and copper clad laminates (such as FR4 epoxy), fan-out wafer level (FOWLP) epoxy molding compounds, or glass. The deposited materials may therefore include layers comprising composite materials disposed on a stabilized core layer including at least one of glass, a polyimide film layer exhibiting an ultra-low isotropic CTE comparable to that of silicon, a reinforcement layer (e.g., aramid fiber reinforced polyimide or fiberglass reinforced epoxy), a ceramic layer, an organic film layer containing a significant amount of ceramic filler, or a non-reinforced epoxy layer.

[0089] The multi-layer material, e.g., the deposited material, can include a glass substrate. Glass substrates are particularly suitable for achieving improved process precision because they exhibit high modulus, excellent dimensional stability, minimal warpage, and relatively low cost. Glass also exhibits an extremely smooth and planar topography. Glass compositions can also be formulated to achieve a coefficient of thermal expansion (CTE) comparable to silicon, and are photoimageable, allowing for photo-definition of vias and strategically placed cavities in the overall design. The composite layer combined with the photo-definable thin glass substrate can provide an optimal combination of low dielectric loss, strategic incorporation of air as a dielectric material, strategic incorporation of cavities to accommodate GPUs, logic, and / or memory chiplets, and / or cooling, multi-layer wiring density including photo-defined vias in both the deposited redistribution composite layer and the glass substrate, precision process, compatible assembly, and subsequent reliability.

[0090] As disclosed herein, the thermosetting composition can include at least one imide-extended compound of formula 1 or formula 2, and a reactive monomer that is free radical crosslinkable with the reactive end groups of the imide-extended compound to produce a crosslinked network. In formula 1 or formula 2, each R can be independently a divalent substituted or unsubstituted aliphatic, alkenyl, aromatic, or heteroaromatic group, or a divalent siloxane group, each Q can be independently a divalent or tetravalent substituted or unsubstituted aliphatic, alkenyl, aromatic, or heteroaromatic group, or a divalent siloxane group, and each R can independently include a reactive alkenyl end group. In formula (1) or formula 2, each R2 can independently include a maleimide group, a citraconimide group, a styryl group, a vinylbenzyl group, a vinyl group, an allyl group, an alkynyl group, a propargyl ether group, a cyano group, a vinyl ether group, a vinyl ester group, an acrylate group, a methacrylate group, an oxazoline group, a benzoxazine group, or a methylnorbornene group. The imide extended compound can include a bismaleimide compound of formula (3). The imide extended compound can include a bisstyryl compound of formula (4). The imide extended compound can include a bisvinylbenzyl compound of formula (5). The imide extended compound can include a bisvinyl compound of formula (6). The imide extended compound can include a bisallyl compound of formula (7). The imide extended compound can include a compound having formula (8). The degree of polymerization of the imide extended compound can be 1 to 100 or 2 to 10. The thermosetting composition can include 10 to 90 volume percent, or 25 to 75 volume percent, or 30 to 50 volume percent of the imide extended compound, based on the total volume of the composition. The reactive monomer can include triallyl (iso)cyanurate. The composition can include 1 to 40 volume percent, or 10 to 35 volume percent, or 20 to 30 volume percent of the reactive monomer, based on the total volume of the composition.

[0091] The thermosetting composition may further include at least one of a free radical initiator, fused silica, functionalized fused silica, a flame retardant, or a ceramic filler. The thermosetting composition may include a free radical initiator. The free radical initiator may be dicumyl peroxide, dimethyldiphenylhexane, methyl ethyl ketone peroxide, cyclohexanone peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,2-bis(t-butylperoxy)butane, t-butyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, t-butyl perbenzoate, α,α'-di-(t-butylperoxy)diisopropanol ... The composition may comprise at least one of the following: 1,4-diisopropylbenzene, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, octanoyl peroxide, isobutyryl peroxide, peroxydicarbonate, α,α'-azobis(isobutyronitrile), redox initiator, acetyl azide, 2,3-dimethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, or poly(1,4-diisopropylbenzene). The composition may comprise 0.1 to 10 volume percent, or 2 to 8 volume percent of the free radical initiator, based on the total volume of the composition. The thermosetting composition may comprise fused silica. The fused silica may have a spherical structural morphology with a median diameter of 1 to 50 micrometers, or 1 to 10 micrometers. The thermosetting composition may comprise a functionalized fused silica that may be chemically coupled into a crosslinked network. The functionalized fused silica may have a spherical structural morphology with a median diameter of 1 to 50 micrometers, or 1 to 10 micrometers. The functional group of the functionalized fused silica may include at least one of a (meth)acrylate group, a vinyl group, an allyl group, a propargyl group, a butenyl group, a styryl group, or a vinylbenzyl group. The functional group of the functionalized fused silica may include a (meth)acrylate group. The thermosetting composition may include 10 to 70 volume percent, or 20 to 60 volume percent, or 30 to 55 volume percent of the fused silica and / or functionalized fused silica, based on the total volume of the composition.The thermosetting composition can include a flame retardant. The flame retardant can be present in an amount of 5 to 25 volume percent, or 8 to 20 volume percent of the flame retardant, based on the total volume of the composition. The thermosetting composition can include a ceramic filler. Ceramic fillers include fumed silica, titanium dioxide, barium titanate, strontium titanate, corundum, wollastonite, Ba2Ti9O. 20 , hollow ceramic spheres, boron nitride, aluminum nitride, silicon carbide, beryllia, alumina, alumina trihydrate, magnesia, mica, talc, nanoclay, or magnesium hydroxide.

[0092] The thermosetting composition can include 10 to 90 volume percent of the imide-extended bismaleimide of formula (8), 1 to 40 volume percent triallyl (iso)cyanurate, 0.1 to 10 volume percent of a free radical initiator, and 10 to 70 volume percent of the methacrylate-functionalized fused silica, the volumes being based on the total volume of the thermosetting composition.

[0093] The thermoset composite may be derived from a thermosetting composition. The composite may have a peel strength to copper of 0.35 kilograms per centimeter or more. The composite may have an average coefficient of thermal expansion in the z-direction of 40 parts per million or less per degree Celsius, or 35 parts per million or less per degree Celsius, from -50 to 150 degrees Celsius. The composite may have a dielectric constant of 2.5 to 3.5 at 10 gigahertz. The composite may have a dielectric loss of 0.0025 or less, or 0.0020 or less, or 0.001 to 0.0025 at 10 gigahertz. The composite may include a reinforcing woven or nonwoven fabric. The reinforcing fabric may include at least one of NE glass fiber, L glass fiber, or quartz fiber. The reinforcing fabric may include at least one of liquid crystal polymer (LCP) fiber, aramid fiber, cyclic olefin copolymer (COC) fiber, or ultra-high molecular weight polyethylene (UHMWPE) fiber. The reinforcing fabric can be an open woven reinforcing fabric. The reinforcing fabric can be present in an amount of 5 to 40 weight percent, or 15 to 25 weight percent, based on the total weight of the thermoset composite.

[0094] The method of making a composite material can include curing a layer formed from the composition. The curing can include at least one of increasing the temperature of the layer, exposing the layer to electron beam radiation, or exposing the layer to ultraviolet (UV) radiation. The method can include forming the layer by casting the composition onto a release liner. The method can include forming the layer by casting the composition onto a metal foil, such as copper or aluminum. The method can include impregnating a reinforcing layer with the composition prior to the curing step.

[0095] The article may include a composite material. The article may be a multi-layer article. The multi-layer article may include at least one of a copper layer, a glass layer, a liquid crystal polymer (LCP) layer, an ultra-low CTE polyimide film layer, a fluoropolymer layer, a ceramic layer, a polyaramid layer, an epoxy layer, or a polyether layer. The article may be an antenna, a bond ply, a stacked film, a circuit board, a resin coated copper foil (RCC), or a flexible core.

[0096] The following examples are provided to illustrate the present disclosure. The examples are merely illustrative and are not intended to limit devices manufactured in accordance with the present disclosure to the materials, conditions, or process parameters referred to herein. EXAMPLES

[0097] In this example, the dielectric constant (Dk) and dielectric loss (Df) (also called loss tangent) were measured according to "Split Post Dielectric Resonator (SPDR) Method for Precision Measurements of Layered Dielectric Specimens" (IEEE Xplore Conference Paper, February 2000) at a temperature of 23-25°C, a relative humidity of 50% and a frequency of 10 gigahertz (GHz).

[0098] Wet and dry film ratings are assigned arbitrarily and relatively, with 0 being the lowest rating and 3 being the highest rating.

[0099] The coefficient of thermal expansion (CTE) in the z-direction was determined in accordance with "Glass Transition Temperature and Thermal Expansion of Materials Used for High Density Interconnects (HDI) and Microvias - TMA Method" (IPC-TM-650 2.4.24.5) and is reported in parts per million per degree Celsius (ppm / °C).

[0100] The elastic modulus was determined in accordance with "Glass Transition and Elastic Modulus of Materials Used for High Density Interconnects (HDI) and Microvias - DMA Method" (IPC-TM-650 2.4.24.4) and is reported in gigapascals (GPa).

[0101] Peel strength was determined in accordance with "Peel Strength of Metal Clad Laminates" (IPC-TM-650 2.4.8) and is reported in pounds per inch (lbs / in).

[0102] Flame retardancy was determined in accordance with Underwriter's Laboratory UL 94 safety standard "Test for Flammability of Plastic Materials Used in Equipment Components," with V0 flame retardancy being the most difficult to achieve and requiring that five specimens of the test material have an average flame-extinguishing time of 5 seconds or less and self-extinguish without dripping. Tests were performed on 6 mil (0.15 mm) thick specimens.

[0103] Ash content was determined by using a high temperature oven to completely decompose and oxidize all organic material in the test samples and determining the amount by weight of the remaining inorganic material.

[0104] The minimum melt viscosity (MMV) was determined using parallel plate oscillatory rheology at a heating rate of 10° C. per minute. The viscosity and temperature at which the film becomes minimally molten and begins to soften before the crosslinker begins to increase molecular weight are taken as the minimum melt viscosity and corresponding temperature.

[0105] In this embodiment, the term 1 oz. copper foil refers to the thickness of the copper layer achieved when 1 oz. (29.6 ml) of copper is pressed flat and spread evenly over an area of ​​one square foot (929 cm. The corresponding thickness is 1.37 mils (0.0347 mm). 1 / 2 oz. copper foil correspondingly has a thickness of 0.01735 mm.

[0106] The ingredients used in this example are shown in Table 1.

[0107] [Table 1]

[0108] Example 1 Preparation of imide-extended composites Thermosetting imide-extended compositions were formed containing 55 wt % solids in toluene as listed in Table 2.

[0109] [Table 2]

[0110] The thermosetting composition was cast onto a 2 mil (50.8 micrometer) poly(ethylene terephthalate) substrate using a knife-over-roll technique. The casting process was carried out at a line speed of 9 ft / min (2.7 meters / min) through four heating zones at increasing temperatures of 180°F (82°C), 220°F (104°C), 220°F (104°C), and 300°F (149°C). The cast composite was then laminated at a temperature of 360°F (182°C) for two hours at a pressure of 0.7 pounds per square inch (4.8 kilopascals).

[0111] Example 2 Preparation of poly(phenylene oxide) (PPO) composites. Thermosetting compositions containing PPO as described in Table 3 were formed.

[0112] [Table 3]

[0113] The thermosetting composition was cast onto a 2 mil poly(ethylene terephthalate) substrate using a knife-over-roll technique. The casting process was carried out at a line speed of 10 ft / min (3 m / min) through four heating zones at increasing temperatures of 150°F (66°C), 200°F (93°C), 220°F (104°C), and 220°F (104°C). The cast composite was then laminated at a temperature of 450°F (232°C) for two hours at a pressure of 0.7 pounds per square inch (4.8 kilopascals).

[0114] Example 3 Comparison of imide-extended and PPO composites. Various properties of the composite materials of Examples 1 and 2 were measured and are provided in Table 4.

[0115] [Table 4]

[0116] Table 4 shows that the imide extended composites have reduced dielectric loss, reduced coefficient of thermal expansion in the z-direction, lower modulus of elasticity, and improved flame retardancy compared to the PPO composites of Example 2.

[0117] In addition, the PPO composite was observed to sag, i.e., stress crack rather than remain flat after the curing step, and was found to be more thermally oxidized compared to the imide-extended composite of Example 1, which remained flat without observable stress cracks. These results can be observed in Figures 1, 2, and 3. Figure 1 is a photographic image of the imide-extended composite of Example 1 lying flat on a table. Figure 2 is a photographic image of the PPO composite of Example 2 being bent as indicated by the arrow pointing to the high corner. Figure 3 is a photographic image of three glass substrates, substrate 0 being uncoated as a reference, substrate 1 being laminated with the imide-extended composite of Example 1, and substrate 2 being laminated with the PPO of Example 2. Substrate 1 is stress crack-free, while substrate 2 exhibits significant stress cracks.

[0118] (Examples 4 to 5) Effect of volume loading of methacrylate fused silica on imide-extended composites Two imide-extended composites were prepared according to Example 1 using the thermosetting compositions as shown in Table 5, and the thermosetting compositions were laminated to the shiny side of an as-received glass substrate and rolled annealed copper (1 / 2 oz. RLD, ultra-low profile) that had been treated with a 1% aqueous sulfuric acid solution prepared by taking 1.05 grams of concentrated sulfuric acid (95-98%) and diluting to 100 mL. Various properties were measured and are shown in Table 5.

[0119] [Table 5]

[0120] These results illustrate the effect of the high volumetric packing fraction of methacrylate fused silica in reducing the resulting coefficient of thermal expansion.

[0121] (Examples 6 to 10) Effect of imide-extended compounds on the CTE-z of the resulting imide-extended composites Five composite materials were prepared using different bifunctional imide extended compounds as shown in Table 6. The resulting properties were determined and are further shown in Table 6.

[0122] [Table 6]

[0123] Table 6 shows that the heat cured composites containing imide extended compound-2 had higher CTE-z values ​​compared to those containing imide extended compound-1. These results illustrate the effect of the imide extended compound on the resulting thermal expansion coefficient.

[0124] Various non-limiting aspects of the disclosure are referenced below.

[0125] Aspect 1: A compound having the following structure:

[0126] [ka]

[0127] wherein R and Q are each independently a divalent substituted or unsubstituted aliphatic, alkenyl, aromatic, heteroaromatic, or divalent siloxane group, and each R2 independently comprises a reactive alkenyl end group, and a reactive monomer that is free radically crosslinkable with the reactive end groups of the imide extended compound to form a crosslinked network.

[0128] Aspect 2: The thermosetting composition of aspect 1, wherein each R2 independently comprises a maleimide group, a citraconimide group, a styryl group, a vinylbenzyl group, a vinyl group, an allyl group, an alkynyl group, a propargyl ether group, a cyano group, a vinyl ether group, a vinyl ester group, an acrylate group, a methacrylate group, an oxazoline group, a benzoxazine group, or a methylnorbornene group.

[0129] Aspect 3: The imide extended compound has the formula:

[0130] [ka]

[0131] 3. The thermosetting composition of claim 1 or 2, comprising a bismaleimide compound of the formula:

[0132] Aspect 4: The imide extended compound has the formula:

[0133] [ka]

[0134] Aspect 4. The thermosetting composition of any one of aspects 1 to 3, comprising a bisstyryl compound of the formula:

[0135] Aspect 5: The imide extended compound has the formula:

[0136] [ka]

[0137] 5. The thermosetting composition of any one of the preceding aspects, comprising a bisvinylbenzyl compound of the formula:

[0138] Aspect 6: The imide extended compound has the formula:

[0139] [ka]

[0140] 6. The thermosetting composition of any one of the preceding embodiments, comprising a bis-vinyl compound of the formula:

[0141] Aspect 7: The imide extended compound has the formula:

[0142] [ka]

[0143] 7. The thermosetting composition of any one of the preceding aspects, comprising a bisallyl compound of the formula:

[0144] Aspect 8: The imide extended compound has the formula:

[0145] [ka]

[0146] wherein n is an integer from 1 to 100, or from 2 to 10.

[0147] Aspect 9: The thermosetting composition of any one or more of Aspects 1 to 8, wherein the composition comprises 10 to 90 volume percent, or 25 to 75 volume percent, or 30 to 50 volume percent of the imide-extended compound, based on the total volume of the composition.

[0148]

[0036] Embodiment 10: The thermosetting composition of any one or more of embodiments 1 to 9, wherein the reactive monomer comprises triallyl (iso)cyanurate.

[0149] Embodiment 11: The thermosetting composition of any one or more of embodiments 1 to 10, wherein the composition comprises 1 to 40 volume percent, or 10 to 35 volume percent, or 20 to 30 volume percent of the reactive monomer, based on the total volume of the composition.

[0150] Aspect 12: The composition further comprising a free radical initiator, the free radical initiator optionally being selected from the group consisting of dicumyl peroxide, dimethyldiphenylhexane, methyl ethyl ketone peroxide, cyclohexanone peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,2-bis(t-butylperoxy)butane, t-butyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, t-butyl perbenzoate, α,α′-di-(t-butylperoxy)diisopropylbenzene, or 2,5-dimethyl-2,5-di(t-butyl 12. The thermosetting composition of any one or more of the preceding aspects, wherein the composition comprises at least one of the following: 1,2-diphenylhexyl ether (peroxy)-3-hexyne, octanoyl peroxide, isobutyryl peroxide, peroxydicarbonate, α,α'-azobis(isobutyronitrile), a redox initiator, acetyl azide, 2,3-dimethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, or poly(1,4-diisopropylbenzene); and / or the composition comprises 0.1 to 10 volume percent, or 2 to 8 volume percent of the free radical initiator, based on the total volume of the composition.

[0151]

[0041] Aspect 13: The thermosetting composition of any one or more of the preceding aspects, further comprising fused silica, the fused silica optionally having a spherical structural morphology having a median diameter of 1 to 50 micrometers, or 1 to 10 micrometers.

[0152]

[0041] Aspect 14: The thermosetting composition of any one or more of the preceding aspects, further comprising a functionalized fused silica capable of being chemically coupled to a crosslinked network, the functionalized fused silica optionally having a spherical structural morphology having a median diameter of 1 to 50 micrometers, or 1 to 10 micrometers.

[0153] Embodiment 15: The thermosetting composition of any one or more of embodiments 1 to 14, wherein the composition comprises 10 to 70 volume percent, or 20 to 60 volume percent, or 30 to 55 volume percent of fused silica, based on the total volume of the composition.

[0154] Embodiment 16: The thermosetting composition of any one or more of embodiments 1 to 15, wherein the composition comprises 10 to 70 volume percent, or 20 to 60 volume percent, or 30 to 55 volume percent of the functionalized fused silica, based on the total volume of the composition.

[0155] Aspect 17: The thermosetting composition of any one or more of the preceding aspects, wherein the fused silica is functionalized with a functional group comprising at least one of a (meth)acrylate group, a vinyl group, an allyl group, a propargyl group, a butenyl group, a styryl group, or a vinylbenzyl group, and preferably the functional group of the functionalized fused silica comprises a (meth)acrylate group.

[0156]

[0041] Aspect 18: The thermosetting composition of any one or more of Aspects 1 to 17, further comprising from 5 to 25 volume percent, or from 8 to 20 volume percent, of a flame retardant, based on the total volume of the composition.

[0157] Aspect 19: The ceramic filler further comprises a ceramic filler, the ceramic filler optionally being selected from the group consisting of fumed silica, titanium dioxide, barium titanate, strontium titanate, corundum, wollastonite, BaTiO 20 19. The thermosetting composition of any one or more of the preceding aspects, comprising at least one of: hollow ceramic spheres, boron nitride, aluminum nitride, silicon carbide, beryllia, alumina, alumina trihydrate, magnesia, mica, talc, nanoclay, or magnesium hydroxide.

[0158] Aspect 20: a compound of the formula:

[0159] [ka]

[0160] 20. The thermosetting composition of any one or more of the previous embodiments, comprising 10 to 90 volume percent of an imide-extended bismaleimide having the formula:

[0161]

[0041] Embodiment 21: A thermoset composite material derived from the thermosetting composition according to any one or more of embodiments 1 to 20.

[0162] Aspect 22: The thermoset composite of aspect 21, wherein the composite has at least one of: a peel strength to copper of 0.35 kilograms per centimeter or greater; an average coefficient of thermal expansion in the z-direction of 40 parts per million or less per degree Celsius or 35 parts per million or less per degree Celsius from -50 to 150 degrees Celsius; a dielectric constant of 2.5 to 3.5 at 10 gigahertz; or a dielectric loss of 0.0025 or less, or 0.0020 or less, or 0.001 to 0.0025 at 10 gigahertz.

[0163]

[0041] Example 23: The thermoset composite of example 21 or 22, further comprising a reinforcing fabric, the reinforcing fabric optionally comprising at least one of NE-glass fiber, L-glass fiber, or quartz fiber, the reinforcing fabric optionally being an open woven reinforcing fabric present in an amount of 5 to 40 weight percent, or 15 to 25 weight percent, based on the total weight of the thermoset composite.

[0164] Aspect 24: The thermoset composite material of any one of aspects 21 to 23, further comprising a reinforcing woven or nonwoven fabric, the reinforcing fabric or nonwoven fabric optionally comprising at least one of liquid crystal polymer (LCP) fibers, aramid fibers, cyclic olefin copolymer (COC) fibers, or ultra-high molecular weight polyethylene (UHMWPE) fibers, and the reinforcing fabric or nonwoven fabric is present in an amount of 5 to 40 weight percent, or 15 to 25 weight percent, based on the total weight of the thermoset composite material.

[0165] Embodiment 25: A method for producing a composite material according to any one of embodiments 21 to 24, comprising a step of curing a layer formed from the composition according to any one or more of embodiments 1 to 19.

[0166] Example 26: The method of example 25, wherein the curing step includes at least one of increasing the temperature of the layer, or exposing the layer to electron beam radiation, or exposing the layer to ultraviolet (UV) radiation.

[0167]

[0041] Embodiment 27: The method of any one or more of embodiments 25 to 26, further comprising forming a layer by casting the composition onto a release liner.

[0168]

[0041] Example 28: The method of any one or more of examples 25 to 27, further comprising forming a layer by casting the composition onto a metal foil, such as copper or aluminum.

[0169]

[0041] Example 29: The method of any one or more of Examples 25 to 28, further comprising the step of impregnating the reinforcing layer with the composition prior to the curing step.

[0170]

[0041] Embodiment 30: A multi-layer article comprising the composite material of any one or more of embodiments 21 to 24.

[0171] Example 31: The multilayer article of example 30, further comprising at least one of a copper layer, a glass layer, a liquid crystal polymer (LCP) layer, an ultra-low CTE polyimide film layer, a fluoropolymer layer, a ceramic layer, a polyaramid layer, an epoxy layer, or a polyether layer.

[0172]

[0046] Example 32: An article comprising the composite material of any one or more of examples 21 to 24.

[0173] Example 33: The article of example 32, which is an antenna, a bond ply, a dielectric film of a stack / redistribution layer of a semiconductor substrate, a circuit board, a resin coated copper foil (RCC), or a flexible core.

[0174] The compositions, methods, and articles can alternatively comprise, consist of, or consist essentially of any suitable materials, steps, or ingredients disclosed herein, and can additionally or alternatively be devised to be devoid of, or substantially free of, any material (or type), step, or ingredient that is not otherwise necessary to achieve the function or purpose of the compositions, methods, and articles.

[0175] As used herein, "a," "an," "the," and "at least one" do not denote limitations of quantity and are intended to cover both the singular and the plural, unless the context clearly indicates otherwise. For example, "an element" has the same meaning as "at least one element," unless the context clearly indicates otherwise. The term "combination" includes blends, mixtures, alloys, reaction products, and the like. Furthermore, "at least one of" means that the recited item includes each element individually, as well as combinations of two or more elements of the recited item, and combinations of at least one element of the recited item with a similar element that is not recited.

[0176] The term "or" means "and / or" unless the context clearly indicates otherwise. References throughout the specification to "an embodiment," "another embodiment," "some embodiments," and the like, mean that a particular element (e.g., a feature, structure, step, or characteristic) described in connection with this embodiment is included in at least one embodiment described herein and may or may not be present in other embodiments. In addition, it should be understood that the described elements may be mixed in any suitable manner in the various embodiments.

[0177] When an element, such as a layer, film, region, or substrate, is referred to as being "on" another element, it can be directly on the other element, or intervening elements may be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.

[0178] Unless otherwise stated herein, all test standards are the latest standards in effect as of the filing date of this application or, if priority is claimed, the filing date of the first priority application in which the test standard appears.

[0179] It should be noted that the amounts of the components of the thermosetting composition, minus any solvent, can directly correspond to their individual amounts in the resulting composite. For example, a composite derived from a thermosetting composition containing 25 vol.% fused silica will itself contain 25 vol.% fused silica based on the total volume of the composite. It should also be noted that the amounts presented herein are based on the total mass or volume of the composition or composite, minus any solvent or reinforcing fabric.

[0180] The endpoints of all ranges referring to the same component or property are inclusive, independently combinable, and include all intermediate endpoints and ranges. For example, a range of "up to 25 vol%, or 5-20 vol%" includes the endpoints and all intermediate values ​​in the range "5-25 vol%," such as 10-23 vol%, etc.

[0181] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.

[0182] Compounds are described using standard nomenclature. For example, any configuration that is not substituted by a indicated group is understood to have its valence filled by the indicated bond or hydrogen atom. A dash ("-") that is not between two letters or symbols is used to indicate the point of attachment of the substituents. For example, -CHO is attached through the carbon of the carbonyl group. As used herein, the term "(meth)acrylic" encompasses both acrylic and methacrylic groups.

[0183] All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in this application contradicts or conflicts with a term in an incorporated reference, the term from this application takes precedence over the conflicting term from the incorporated reference.

[0184] While specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents, either now or presently unforeseen, may occur to applicant or others skilled in the art, and it is accordingly intended that the appended claims shall embrace all such alternatives, modifications, improvements, and substantial equivalents as filed and as they may be amended.

Claims

1. The following structure: 【Chemistry 1】 (In the formula, R and Q are each independently a divalent substituted or unsubstituted aliphatic group, alkenyl group, aromatic group, heterocyclic aromatic group, or divalent siloxane group, and each R 2 each independently contains a reactive alkenyl end group and an imide-extended compound of a reactive end group of the imide extended compound and a reactive monomer that is free radical crosslinkable to produce a crosslinked network; 1. A thermosetting composition comprising:

2. Each R 2 independently comprise a maleimide group, a citraconimide group, a styryl group, a vinylbenzyl group, a vinyl group, an allyl group, an alkynyl group, a propargyl ether group, a cyano group, a vinyl ether group, a vinyl ester group, an acrylate group, a methacrylate group, an oxazoline group, a benzoxazine group, or a methylnorbornene group.

3. The imide extended compound has the formula: 【Chemistry 2】 3. The thermosetting composition according to claim 1, comprising a bismaleimide compound represented by the formula:

4. The imide extended compound has the formula: 【Chemistry 3】 4. The thermosetting composition according to claim 1, comprising a bisstyryl compound of the formula:

5. The imide extended compound has the formula: 【Chemistry 4】 5. The thermosetting composition according to claim 1, comprising a bisvinylbenzyl compound of the formula:

6. The imide extended compound has the formula: 【Chemistry 5】 6. The thermosetting composition according to claim 1, comprising a bis-vinyl compound of the formula:

7. The imide extended compound has the formula: 【Chemistry 6】 7. The thermosetting composition according to claim 1, comprising a bisallyl compound of the formula:

8. The imide extended compound has the formula: 【Chemistry 7】 (wherein n is an integer from 1 to 100, or from 2 to 10).

8. The thermosetting composition of claim 1 , comprising a compound having the formula:

9. 9. The thermosetting composition of claim 1, wherein the composition comprises from 10 to 90 volume percent, or from 25 to 75 volume percent, or from 30 to 50 volume percent of the imide-extended compound, based on the total volume of the composition.

10. 10. The thermosetting composition of claim 1, wherein the reactive monomer comprises triallyl (iso)cyanurate.

11. 11. The thermosetting composition of any one of claims 1 to 10, wherein the composition comprises from 1 to 40 volume percent, or from 10 to 35 volume percent, or from 20 to 30 volume percent of the reactive monomer, based on the total volume of the composition.

12. further comprising a free radical initiator; The free radical initiator is optionally selected from the group consisting of dicumyl peroxide, dimethyldiphenylhexane, methyl ethyl ketone peroxide, cyclohexanone peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,2-bis(t-butylperoxy)butane, t-butyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, t-butyl perbenzoate, α,α'-di-(t-butylperoxy)diisopropyl and / or at least one of 1,4-diisopropylbenzene, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, octanoyl peroxide, isobutyryl peroxide, peroxydicarbonate, α,α'-azobis(isobutyronitrile), a redox initiator, acetyl azide, 2,3-dimethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, or poly(1,4-diisopropylbenzene); 12. The thermosetting composition of any one of claims 1 to 11, wherein the composition comprises 0.1 to 10 volume percent, or 2 to 8 volume percent, of the free radical initiator, based on the total volume of the composition.

13. 13. The thermosetting composition of any one of claims 1 to 12, further comprising fused silica, the fused silica optionally having a spherical structural morphology having a median diameter of 1 to 50 micrometers, or 1 to 10 micrometers.

14. 14. The thermosetting composition of any one of claims 1 to 13, further comprising a functionalized fused silica capable of being chemically coupled to a crosslinked network, the functionalized fused silica optionally having a spherical structural morphology with a median diameter of 1 to 50 micrometers, or 1 to 10 micrometers.

15. 15. The thermosetting composition of any one of claims 1 to 14, wherein the composition comprises from 10 to 70 volume percent, or from 20 to 60 volume percent, or from 30 to 55 volume percent of fused silica, based on the total volume of the composition.

16. 16. The thermosetting composition of any one of claims 1 to 15, wherein the composition comprises from 10 to 70 volume percent, or from 20 to 60 volume percent, or from 30 to 55 volume percent of the functionalized fused silica, based on the total volume of the composition.

17. 17. The thermosetting composition of any one of claims 1 to 16, wherein the fused silica is functionalized with a functional group comprising at least one of a (meth)acrylate group, a vinyl group, an allyl group, a propargyl group, a butenyl group, a styryl group, or a vinylbenzyl group, preferably the functional group of the functionalized fused silica comprises a (meth)acrylate group.

18. 18. The thermosetting composition of any one of claims 1 to 17, further comprising from 5 to 25 volume percent, or from 8 to 20 volume percent, of a flame retardant, based on the total volume of the composition.

19. The ceramic filler may further comprise a ceramic filler, which may optionally be selected from the group consisting of fumed silica, titanium dioxide, barium titanate, strontium titanate, corundum, wollastonite, Ba 2 Ti 9 O 20 19. The thermosetting composition of any one of claims 1 to 18, comprising at least one of hollow ceramic spheres, boron nitride, aluminum nitride, silicon carbide, beryllia, alumina, alumina trihydrate, magnesia, mica, talc, nanoclay, or magnesium hydroxide.

20. formula: 【Chemistry 8】 and 10 to 90 volume percent of an imide-extended bismaleimide having 1 to 40 volume percent triallyl (iso)cyanurate; 0.1 to 10 volume percent of a free radical initiator; 10 to 70 volume percent of methacrylate-functionalized fused silica; Including, 20. The thermosetting composition of claim 1, wherein the volume is based on the total volume of the thermosetting composition.

21. 21. A thermoset composite material derived from the thermosetting composition according to any one of claims 1 to 20.

22. Peel strength to copper of 0.35 kilograms per centimeter or more; an average coefficient of thermal expansion in the z-direction of less than or equal to 40 parts per million per degree Celsius, or less than or equal to 35 parts per million per degree Celsius, from -50 to 150 degrees Celsius; A dielectric constant between 2.5 and 3.5 at 10 GHz, or At 10 GHz, dielectric loss of 0.0025 or less, or 0.0020 or less, or 0.001 to 0.0025 22. The thermoset composite material of claim 21, comprising at least one of:

23. Further comprising a reinforcing fabric, the reinforcing fabric optionally comprises at least one of NE-glass fiber, L-glass fiber, or quartz fiber; 23. The thermoset composite of claim 21 or 22, wherein the reinforcing fabric is optionally an open woven reinforcing fabric present in an amount of 5 to 40 weight percent, or 15 to 25 weight percent, based on the total weight of the thermoset composite.

24. Further comprising a reinforcing woven or nonwoven fabric, the reinforcing fabric or nonwoven optionally comprises at least one of liquid crystal polymer (LCP) fibers, aramid fibers, cyclic olefin copolymer (COC) fibers, or ultra-high molecular weight polyethylene (UHMWPE) fibers; 24. The thermoset composite of any one of claims 21 to 23, wherein the reinforcing fabric or nonwoven fabric is present in an amount of 5 to 40 weight percent, or 15 to 25 weight percent, based on the total weight of the thermoset composite.

25. Curing the layer formed from the composition according to any one of claims 1 to 20.

25. A method for producing the composite material of any one of claims 21 to 24, comprising:

26. 26. The method of claim 25, wherein the curing step comprises at least one of increasing the temperature of the layer, or exposing the layer to electron beam radiation, or exposing the layer to ultraviolet (UV) radiation.

27. 27. The method of claim 25 or 26, further comprising forming the layer by casting the composition onto a release liner.

28. 28. The method of any one of claims 25 to 27, further comprising forming a layer by casting the composition onto a metal foil, such as copper or aluminum.

29. 28. The method of any one of claims 25 to 27, further comprising the step of impregnating the reinforcing layer with the composition prior to the curing step.

30. 25. A multi-layer article comprising the composite material of any one of claims 21 to 24.

31. 31. The multilayer article of claim 30, further comprising at least one of a copper layer, a glass layer, a liquid crystal polymer (LCP) layer, an ultra-low CTE polyimide film layer, a fluoropolymer layer, a ceramic layer, a polyaramid layer, an epoxy layer, or a polyether layer.

32. 25. An article comprising the composite material of any one of claims 21 to 24.

33. 33. The article of claim 32, which is an antenna, a bond ply, a dielectric film of a stack / redistribution layer of a semiconductor substrate, a circuit board, a resin coated copper foil (RCC), or a flexible core.